EVALUASI KEBUTUHAN PENGEMBANGAN KURIKULUM BLOK BERTEMA BERBASIS OBE: STUDI PERSEPSI MAHASISWA DAN DOSEN DI PENDIDIKAN BISNIS - Hasibuan, Novita Indah; Baskoro, Danny Ajar; Poluan, Nadia Amelia Elyana; Handriyani, Richna (STKIP Pesisir Selatan, 2025)
The implementation of Industrial Revolution 4.0 and Society 5.0 demands curriculum changes in the Business Education Study Program of Medan State University (UNIMED) to create graduates who have pedagogical skills and digital entrepreneurship expertise. This study aims to analyze students' and lecturers' perceptions of the effectiveness of the Outcome-Based Education (OBE)-based block curriculum and evaluate the need for more integrated thematic curriculum development. The method used is a mixed methods approach with a survey of 115 students semester 3-5 and 7 lecturers, as well as in-depth interviews, complemented by descriptive statistical and thematic analysis. The results showed 68% of students considered the eight-week duration of the block system inadequate for project-based learning; only 41% of respondents saw a clear link between courses in a block; the proportion of skills assessment of 38% did not meet OBE standards; and collaboration with industry was still limited only in 28% of blocks. Project-Based Learning received high satisfaction (82%), but the use of digital technology is still low. In conclusion, the main results revealed, among others, that block duration needs to be adjusted, especially for practicum projects; thematic learning should combine related courses (integration of marketing, entrepreneurship, and pedagogy.